First Annual Short Course in Educational Leadership : Littledale Conference Centre, St. John's, Newfoundland, February 22-27,1987. Day 5. Plenary session. Tape 3 of 6 - Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology, 1987)
A mock case based on the arbitration board hearing in Manitoba of Amaranth School Committee v. Turtle River School Division is enacted. At issue is the failure of the school to provide an adequate education by failing to recognize the special culture and educational needs of their Métis students resulting in a high rate of dropouts. Players in the mock case are: Beverley LeMoine, Richard Harvey, Reg Bonnell, Thomosina Cleal, Pamela Walsh, William Lee, Bill Whelan, Linda Doody, and Mary Power. The arbitration board is played by Dr. Michael Manley-Casimir, Dr. Romulo Magsino and Dr. Phil Warren.